Horizontal impulse generation characteristics during the sprint start are influenced by shank segment control - Costa, K. E.; McNitt-Gray, J. L. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Rate of horizontal force development was not found to be directly related to horizontal impulse generation during the first step of a sprint start. Individual horizontal impulse generation characteristics (e.g. large sum Fh over short delta t, or small sum Fh over long delta t) appears to be related to lower extremity segment control at touchdown and during ground contact phase.